Peran Kepala Sekolah Dalam Meningkatkan Manajemen Mutu Peserta Didik di SDN 015 Samarinda Ulu - Ningsih, Rina Novita; Mukrima (El-Idare, 2024)
This research discusses the role of the school principal in improving the quality management of students at SDN 015 Samarinda Ulu. Through a qualitative approach using interviews and observations as data collection techniques, this study explores the strategies and steps taken by the school principal to advance education in the school. The research findings indicate that the school principal plays a central role in developing the school's vision, mission, and policies, as well as in implementing programs aimed at improving the quality of education. The school principal also plays a role in evaluating and monitoring school performance, using evaluation results to guide sustainable performance monitoring. The results of this study show that the school principal at SDN 015 Samarinda Ulu is not only an administrator but also a visionary leader and effective agent of change in improving the quality management of students. The implications of this research emphasize the importance of the school principal's role in managing and advancing education at the elementary school level, as well as the need for support and cooperation from all education stakeholders.